Macrophage colony‐stimulating factor plays a pivotal role in chemically induced hepatocellular carcinoma in mice. Issue 7 (25th June 2013) - Hara, Michio; Kono, Hiroshi; Furuya, Shinji; Hirayama, Kazuyoshi; Tsuchiya, Masato; Fujii, Hideki
<x xml:space="preserve">Abstract</x> Aim The specific purpose of this study was to investigate the role of macrophage colony‐stimulating factor (M‐CSF) in initiation and progression of hepatocellular carcinoma using M‐CSF‐deficient mice. Methods M‐CSF‐deficient (osteopetrotic: op/op) and their littermate (LM) mice were i.p. injected with diethylnitrosamine (DEN) to induce hepatocellular carcinoma. Twenty‐eight weeks after DEN administration, the tumor incidence rate and serum M‐CSF levels were assessed. Furthermore, distribution of the activated macrophages and the mRNA expression of CD163 and CD204 were evaluated. Moreover, angiogenesis was analyzed in tumors. In another set of experiments, apoptosis and proliferation of the hepatocytes were examined in the acute phase after DEN administration. Isolated hepatic macrophages were cultured with or without M‐CSF, and vascular endothelial growth factor (VEGF) production was assessed by enzyme‐linked immunoassay. Results Tumor incidence was significantly reduced in the op/op compared with the LM mice. Serum M‐CSF levels were increased in the carcinogenesis models of the LM mice. Hepatic macrophages were found only in tumors in the op/op but in both normal liver tissue and tumors in the LM mice. In the op/op group, the mRNA expression of inflammatory cytokines was significantly lower compared with the LM mice. Furthermore, apoptosis was significantly increased in the op/op than the LM mice. Angiogenesis increased in liver tumors from the LM compared with the op/op mice. Production of VEGF was greater in the hepatic macrophages incubated with M‐CSF compared with those without M‐CSF. Conclusion Thus, M‐CSF is involved in the progression of chemically induced hepatocarcinogenesis.